Pengaruh Brand Ambassador Terhadap Purchase Decision OPPO Smartphone di Kota Sukabumi - Sifa Wajhillah; Umban Adi Jaya; Sherra Adistiana Rizki Utami (Winter Journal: IMWI Student Research Journal, 2022)
This study aims to determine the effect of Brand Ambassador on OPPO Smartphone Purchase Decisions in Sukabumi City. This type of research is categorized as a descriptive study using a quantitative approach. The population of this research is OPPO smartphone users in Sukabumi City. The research sample was 100 respondents who had purchased the product. Selection of the research sample using purposive sampling technique. The data was collected using a questionnaire instrument. Testing instruments using validity and reliability tests. Meanwhile, the data analysis was carried out by using classical assumption test and multiple linear regression test. The results showed that the brand ambassador variable had a positive and significant effect on the purchasing decision variable. Dominant respondents pay attention to the factors of visibility and attractiveness of the brand ambassador.